(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
The results of this study indicate that the RI Attorney General’s Office is a government apparatus in the field of law enforcement who does not only carry out criminal duties, but is also charged with other duties in the civil sector and TUN as State Attorney Attorney as stated in Law Number 16 of 2004 concerning RI Attorney Article 30 paragraph 2. The Attorney General’s Office as State Attorney Attorney can act inside or outside the court for and or the name of the government to provide legal assistance, law enforcement, legal considerations and other legal actions. However, this role has not been widely used by local governments. This research discusses how the role of the prosecutor as state lawyer in the efforts to restore and save the country’s wealth and what efforts the prosecutor as the state attorney has made in restoring and saving state assets related to the island of heaven. The method used in this paper is normative legal research using statutory approaches, conceptual approaches and historical approaches. The legal materials used are primary legal materials and secondary legal materials, then the data processing techniques use qualitative processing techniques. The results showed that the role of the prosecutor as state lawyer in the efforts to restore and save state assets related to the island of Khayangan shows very satisfying results. However, the role of prosecutors as state lawyers to represent local government agencies is still minimal and not all of the functions of state attorneys are used by stakeholders. As for the efforts made by the State Attorney in the recovery and rescue related to the island of Khayangan, namely by using a persuasive approach, where the state attorney as the mediator in the mediation process uses a persuasive approach. Then the state attorney’s attorney suggested to resolve the dispute over the management of this island in non litigation.